Tumor Cell‐Responsive Photodynamic Immunoagent for Immunogenicity‐Enhanced Orthotopic and Remote Tumor Therapy. Issue 5 (27th November 2022) - Chen, Yingchao; Xiong, Tao; Zhao, Xueze; Du, Jianjun; Sun, Wen; Fan, Jiangli; Peng, Xiaojun
Abstract: Combining photodynamic therapy (PDT) and immune checkpoint blockades is an efficient method to maximize immunotherapeutic outcome by boosting tumor immunogenicity and modulating the immunosuppressive tumor microenvironment. However, the always‐on bioactivity of photosensitizers or immune checkpoint inhibitors leads to uncontrollable side effects, limiting the in vivo therapeutic efficacy of treatments. An activatable strategy is of great importance for improving the selectivity during cancer therapy. In this study, a photodynamic immunomodulator, ICy‐NLG, is developed by conjugating the photosensitizer ICy‐NH2 with the indoleamine 2, 3‐dioxygenase 1 inhibitor NLG919 through a glutathione (GSH)‐cleavable linker to achieve activatable photodynamic immunotherapy. The conjugation considerably suppresses both the PDT effect and the activity of the inhibitor. After ICy‐NLG is activated by high levels of GSH in tumor cells, the PDT effect is restored and leads to immunogenic tumor cell death. The released tumor‐associated antigens in conjunction with the activated immune checkpoint inhibitor induce a synergistic antitumor immune response, resulting in the growth inhibition of primary and distant tumors and the prevention of lung metastasis in mouse xenograft models. Abstract : The activatable photodynamic immunoagent, ICy‐NLG, realizes the specificity to tumor cells and avoids severe side effects caused by the always‐on bioactivity of photosensitizers or immunotherapy drugs. After being activated by overexpressed glutathione in tumor cells, the restored PDT and released ICB drug achieve efficient synergistic therapy in mouse xenograft models by boosting the immunogenicity and inducing antitumor immune response.